Phase I study of continuous MKC-1 in patients with advanced or metastatic solid malignancies using the modified Time-to-Event Continual Reassessment Method (TITE-CRM) dose escalation design - Tevaarwerk, Amye; Wilding, George; Eickhoff, Jens; Chappell, Rick; Sidor, Carolyn; Arnott, Jamie; Bailey, Howard; Schelman, William; Liu, Glenn (Investigational new drugs, 2012)
Summary Background MKC-1 is an oral cell-cycle inhibitor with broad antitumor activity in preclinical models. Clinical studies demonstrated modest antitumor activity using intermittent dosing schedule, however additional preclinical data suggested continuous dosing could be efficacious with additional effects against the mTor/AKT pathway. The primary objectives were to determine the maximum tolerated dose (MTD) and response of continuous MKC-1. Secondary objectives included characterizing the dose limiting toxicities (DLTs) and pharmacokinetics (PK). Methods Patients with solid malignancies were eligible, if they had measurable disease, ECOG PS ≤1, and adequate organ function. Exclusions included brain metastases and inability to receive oral drug. MKC-1 was dosed twice daily, continuously in 28-day cycles. Other medications were eliminated if there were possible drug interactions. Doses were assigned using a TITE-CRM algorithm following enrollment of the first 3 pts. Disease response was assessed every 8 weeks. Results Between 5/08–9/09, 24 patients enrolled (15 M/9 F, median 58 years, range 44–77). Patients 1–3 received 120 mg/d of MKC-1; patients 4–24 were dosed per the TITE-CRM algorithm: 150 mg [ n = 1], 180 [2], 200 [1], 230 [1], 260 [5], 290 [6], 320 [5]. The median time on drug was 8 weeks (range 4–28). The only DLT occurred at 320 mg (grade 3 fatigue). Stable disease occurred at 150 mg/d (28 weeks; RCC) and 320 mg/d (16 weeks; breast, parotid). Escalation halted at 320 mg/d. Day 28 pharmacokinetics indicated absorption and active metabolites. Conclusion Continuous MKC-1 was well-tolerated; there were no RECIST responses, although clinical benefit occurred in 3/24 pts. Dose escalation stopped at 320 mg/d, and this is the MTD as defined by the CRM dose escalation algorithm; this cumulative dose/cycle exceeds that determined from intermittent dosing studies. A TITE-CRM allowed for rapid dose escalation and was able to account for late toxicities with continuous dosing via a modified algorithm.